Phylogenomic Signatures of Ancient Introgression in a Rogue Lineage of Darters (Teleostei: Percidae). (3rd December 2018) - MacGuigan, Daniel J; Near, Thomas J
Abstract: Evolutionary history is typically portrayed as a branching phylogenetic tree, yet not all evolution proceeds in a purely bifurcating manner. Introgressive hybridization is one process that results in reticulate evolution. Most known examples of genome-wide introgression occur among closely related species with relatively recent common ancestry; however, we present evidence for ancient hybridization and genome-wide introgression between major stem lineages of darters, a species-rich clade of North American freshwater fishes. Previous attempts to resolve the relationships of darters have been confounded by the uncertain phylogenetic resolution of the lineage Allohistium . In this study, we investigate the phylogenomics of darters, specifically the relationships of Allohistium, through analyses of approximately 30, 000 RADseq loci sampled from 112 species. Our phylogenetic inferences are based on traditional approaches in combination with strategies that accommodate reticulate evolution. These analyses result in a novel phylogenetic hypothesis for darters that includes ancient introgression between Allohistium and other two major darter lineages, minimally occurring 20 million years ago. Darters offer a compelling case for the necessity of incorporating phylogenetic networks in reconstructing the evolutionary history of diversification in species-rich lineages. We anticipate that the growing wealth of genomic data for clades of non-model organisms will reveal more examples of ancient hybridization, eventually requiring a re-evaluation of how evolutionary history is visualized and utilized in macroevolutonary investigations.